Protein deficiency during pregnancy and lactation impairs glucose-induced insulin secretion but increases the sensitivity to insulin in weaned rats - Latorraca, M. Q.; Carneiro, E. M.; Boschero, A. C.; Mello, MAR (C A B International, 1998)
We studied glucose homeostasis in rat pups from darns fed on a normal-protein (170 g/kg) (NP) diet or a diet containing 60 g protein/kg (LP) during fetal life and the suckling period. At birth, total serum protein, serum albumin and serum insulin levels were similar in both groups. However, body weight and serum glucose levels in LP rats were lower than those in NP rats. At the end of the suckling period (28 d of age), total serum protein, serum albumin and serum insulin were significantly lower and the liver glycogen and serum free fatty acid levels were significantly higher in LP rats compared with NP rats. Although the fasting serum glucose level was similar in both groups, the area under the blood glucose concentration curve after a glucose load was higher for NP rats (859 (SEM 58) mmol/l per 120 min for NP rats v. 607 (SEM 52) mmol/l per 120 min for LP rats; P < 0.005). The mean post-glucose increase in insulin was higher for NP rats (30 (SEM 4.7) nmol/l per 120 min for NP rats v. 17 (SEM 3.9) nnol/l per 120 min for LP rats; P < 0.05). The glucose disappearance rate for NP rats(0.7 (SEM 0.1) %/min) was lower than that for LP rats (1.6 (SEM 0.2) %/min; P < 0.001). Insulin secretion from isolated islets (1 h incubation) in response to 16.7 mmol glucose/l was augmented 14-fold in NP rats but only 2.6-fold in LP rats compared with the respective basal secretion (2.8 mmol/l; P <0.001). These results indicate that in vivo as well as in vitro insulin secretion in pups from dams maintained on a LP diet is reduced. This defect may be counteracted by an increase in the sensitivity of target tissues to insulin.
Keywords: protein malnutrition; insulin; glucose homeostasis